Mathematics at Your Fingertips: Testing a Finger Training Intervention to Improve Quantitative Skills - Jay, Tim; Betenson, Julie (Frontiers in Education, 2017)
Previous research indicates that the use of fingers as representations of ordinal and cardinal number is an important part of young children's mathematics learning. Further to this, some studies have shown that a finger training intervention can improve young children's quantitative skills. In this article, we argue that fingers represent a means for children to bridge between different external representations of number (including verbal, symbolic and non-symbolic representations). Therefore we predicted that an intervention that combined finger training with experience playing games involving multiple representations would lead to greater increases in quantitative skills than either aspect of the intervention alone. One hundred and thirty-seven children aged between six and seven years old took part in an intervention study over the course of four weeks. The study tested the impact of five different conditions on participants' quantitative skills, their finger gnosis, and their ability to compare magnitudes of two non-symbolic representations of number. Relative to a control group, those children receiving a finger training intervention saw gains in finger gnosis skills (the ability to differentiate fingers when touched, without visual cues). Those children who played number games saw an increase in their non-symbolic magnitude comparison skills. However, only those children who experienced both aspects of the intervention saw increases in quantitative skills, which were assessed using an instrument informed by Gelman and Gallistel's (1978) five principles of counting. The findings show that a finger training intervention, when combined with intensive exposure to multiple representations of number, can support young children's development of quantitative skills. This adds to evidence in the literature regarding the role of fingers in children's mathematics learning, and may have implications for pedagogical approaches.